PERANCANGAN SISTEM PENGOLAHAN DATA PANEN BERBASIS WEB PADA KELOMPOK TANI HARVEST MIND - Minda Mora Purba; Ilham Katuju (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2023)
ABSTRACTIn the digital age, information has become a staple and a new commodity. The use of information technology is needed in helping to support performance to meet needs. In the field of data processing, information technology plays a very important role. The presence of information technology can make it easier for farmers to process data through information systems. This research discusses the design of a data processing system in one of the farmer groups, because data processing currently still uses manual methods that take longer. By using the SDLC Waterfall method and using the PHP programming language and MySQL database, this application can be designed easily. This research has produced a harvest data processing system that farmers can use in processing their harvest data. In addition, the system interface is implemented according to the data that is usually processed so that the system can be used easily.Â Keywords : field of data processing, waterfall, php, mysql, web